Breastfeeding Experiences by Mothers with Covid-19: Lessons from the Pandemic for the Better Future - Kusuma, Nur Intan; Mufdlilah, Mufdlilah; Suryaningsih, Endang Koni (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: The spread of COVID-19 had affected disruption of health care system including maternal and neonatal health care, one of which was breastfeeding services. Breastfeeding mothers with COVID-19 needed more attention because they experienced separation, lack of skin-to-skin contact, and insufficient support. Purpose: This scoping review aimed to map the literature, identify knowledge gap and conduct review of scientific evidence about breastfeeding by COVID-19 mothers. Method: The scoping review method applied PRISMA-ScR guideline. Five databases were used to search relevant articles using PEOS framework. Result: From this search, 723 articles were obtained and 11 articles that appropriate with the inclusion criteria. Six themes were found in this scoping review, namely breastfeeding for baby, safety of breastfeeding, the barriers to breastfeeding COVID-19, the motivation of COVID-19 mother in breastfeeding, condition of breastfeeding mothers with COVID-19 and social support. Conclusion: The importance of breastfeeding by mothers with COVID-19 must be understood by families, health workers and health service providers as an effort to achieve breastfeeding by mothers with COVID-19.